2010
DOI: 10.1007/s10886-010-9758-6
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in the Plant, Barbarea vulgaris, and Counter-Adaptations in Flea Beetles Mediated by Saponins

Abstract: Three saponins and two sapogenins had differential effects on food consumption in five near-isogenic flea beetle lines, which differ in their ability to utilize a novel host plant, Barbarea vulgaris (Brassicaceae). The ability to live on this plant is controlled by major, dominant R-genes in the flea beetle, Phyllotreta nemorum (Coleoptera: Chrysomelidae: Alticinae). A susceptible genotype (rr) is unable to live on the plant, whereas resistant genotypes (RR and Rr) can utilize the novel host plant. Among compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…Alternatively, glucosylated saponins may have a more adverse taste for insects than the corresponding sapogenins (Glendinning, 2002); however, P. nemorum larvae die from exposure to G-type leaves (Nielsen, 1997a). Nielsen et al (2010) suggested that cleavage of the b-1,4-glycosidic bond in the cellobiosides by bglucosidases allows resistant P. nemorum lines to feed on G-type B. vulgaris. This mechanism would be similar to what has been found for fungal adaptation to saponins (Osbourn et al, 1991;Wubben et al, 1996;Pareja-Jaime et al, 2008).…”
Section: -O-glucosylation Of Hederagenin Deters Feeding By P Nemorummentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, glucosylated saponins may have a more adverse taste for insects than the corresponding sapogenins (Glendinning, 2002); however, P. nemorum larvae die from exposure to G-type leaves (Nielsen, 1997a). Nielsen et al (2010) suggested that cleavage of the b-1,4-glycosidic bond in the cellobiosides by bglucosidases allows resistant P. nemorum lines to feed on G-type B. vulgaris. This mechanism would be similar to what has been found for fungal adaptation to saponins (Osbourn et al, 1991;Wubben et al, 1996;Pareja-Jaime et al, 2008).…”
Section: -O-glucosylation Of Hederagenin Deters Feeding By P Nemorummentioning
confidence: 99%
“…The resistance of G-type B. vulgaris against herbivorous insects, such as P. xylostella and susceptible P. nemorum, has previously been shown to depend on the presence of saponins, and especially hederagenin and oleanolic acid cellobioside, which are absent in the susceptible P-type (Shinoda et al, 2002;Agerbirk et al, 2003a;Kuzina et al, 2009;Nielsen et al, 2010). Therefore, the synthesis of saponins was initially thought to be unique to the G-type.…”
Section: -O-glucosylation Of Hederagenin Deters Feeding By P Nemorummentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of cardiac glycosides reaffirms their use a traditional medicine.Saponins are produced by plants to protect them against pathogens and herbivory. They have been found to kill fungus, insects and molluscs that attack plants and also act as allelopathic [62][63][64]. Saponins also act as anticancerous, and antiangiogenic agents and have been reported to inhibit the progression of the cell cycle and induce apoptosis [65].…”
Section: Discussionmentioning
confidence: 99%
“…Saponins also act as anticancerous, and antiangiogenic agents and have been reported to inhibit the progression of the cell cycle and induce apoptosis [65]. The other activities attributed to saponins include antioxidant, anticarcinogenic, immunostimulatory, antibacterial, antifungal, antiviral, antiprotozoal, hypoglycemic, hemolytic, immune adjuvant and membrane permeabilizing [62,63,64]. The saponins were present in all the extracts of O. indicum, and M. pachycarpa, except the chloroform extract of the former.…”
Section: Discussionmentioning
confidence: 99%